Marketing and consumption of art products: the movie industry - Ulker-Demirel, Elif; Akyol, Ayse; Simsek, Gulhayat Golbasi (EMERALD GROUP PUBLISHING LTD, 2018)
Purpose The purpose of this paper is to investigate the impact of the importance, assigned by audiences, of factors such as people, movie features, script, price, promotion, and distribution channels (defined as a movie marketing mix) on the audience's buying intentions, as well as the impact of their buying intentions on word of mouth (WOM). In addition, the intention is to explore the relationship between the preference and frequency of people's cultural event attendance with their buying intention and the relationship between people with extroverted personalities and WOM. Design/methodology/approach The data were collected from 904 valid surveys conducted in Beyoglu, one of the important centres for the culture and art life of the Istanbul. Findings The results show that promotion, actor or actress, and diversity of distribution channels have a positive effect on people's purchase intention. In addition, the frequency of attendance to cultural events can be determinative of the audience and helpful for industry professionals. Originality/value Although there have been a number of studies that examine the simple relationships among some of these variables (movie marketing mix, attendance, purchase intention, WOM, extraversion), there is still a gap in the literature with regard to these variables in an integrated framework. Considering these variables in the same model and analysing the effects of each dimension individually provides a better explanation of consumer purchase intention and post-purchase behaviour in the movie industry. This study extends the previous research by incorporating the concept of movie marketing and consumption by improving the scale with data collected in Istanbul, Turkey.
Keywords: Attendance; Structural equation modelling (SEM); Movie marketing; Movie marketing mix; WORD-OF-MOUTH; FILM-CRITICS; FIT INDEXES; EXPERIENCE; MODEL; REVIEWS; SUCCESS; DETERMINANTS; SATISFACTION; SERVICE; Business & Economics